Face masks increase compliance with physical distancing recommendations during the COVID-19 pandemic - Gyula Seres; Anna Helen Balleyer; Nicola Cerutti; Anastasia Danilov; Jana Friedrichsen; Yiming Liu; Müge Süer (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2020)
Governments across the world have implemented restrictive policies to slow the spread of COVID-19. Recommended face mask use has been a controversially discussed policy, among others, due to potential adverse effects on physical distancing. Using a randomized field experiment (N=300), we show that individuals keep a significantly larger distance from someone wearing a face mask than from an unmasked person. According to an additional survey experiment (N=456), masked individuals are not perceived as being more infectious than unmasked ones, but they are believed to prefer more distancing. This result suggests that, in times where mask use is voluntary, wearing a mask serves as a social signal for a preferred greater distance that is respected by others. Our findings provide strong evidence against the claim that mask use creates a false sense of security that would negatively affect physical distancing.
Keywords: C93; D9; I12; 330; COVID-19; Health Policy; Compliance; Face Masks; Risk Compensation; Field Experiment